1995
DOI: 10.1002/ijc.2910620619
|View full text |Cite
|
Sign up to set email alerts
|

Amphiregulin anti‐sense oligodeoxynucleotides inhibit growth and transformation of a human colon carcinoma cell line

Abstract: Amphiregulin (AR) is a secreted heparin-binding growth factor that is structurally and functionally related to epidermal growth factor (EGF) and transforming growth factor alpha (TGF alpha). GEO cells are from a human colon cancer cell line that expresses high levels of AR protein and mRNA. To assess the role of AR in colon-cancer cell proliferation and transformation, 2 different anti-sense 20-mer phosphorothioate oligodeoxynucleotides (AR AS-1 and AR AS-2 S-oligos) complementary to the 5' sequence of AR mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…We have previously demonstrated that AS PS-oligos directed against TGFa, AR and CR are able to inhibit the in vitro anchorage independent growth (AIG) of GEO colon carcinoma cells Normanno et al, 1995bNormanno et al, , 1996. We developed novel, antisense mixed backbone oligonucleotides (AS MBOs) directed against the EGF-related growth factors, starting from the sequence of the above mentioned AS PS-oligos (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that AS PS-oligos directed against TGFa, AR and CR are able to inhibit the in vitro anchorage independent growth (AIG) of GEO colon carcinoma cells Normanno et al, 1995bNormanno et al, , 1996. We developed novel, antisense mixed backbone oligonucleotides (AS MBOs) directed against the EGF-related growth factors, starting from the sequence of the above mentioned AS PS-oligos (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Direct evidence that TGFa, AR and CR can function as autocrine growth factors in colon carcinoma cells in vitro has been established by using either neutralizing monoclonal antibodies or by utilizing antisense phosphorothioate oligodeoxynucleotides (AS PS-oligos), or antisense mRNA retroviral expression vectors directed against these growth factors (Sizeland and Burgess, 1992;Watkins et al, 1991;Ciardiello et al, 1993Normanno et al, 1995bNormanno et al, , 1996. The present study was designed to evaluate the role of TGFa, AR and CR in the in vivo growth of human GEO colon carcinoma cells, and to assess whether these EGF-related peptides might represent suitable targets for experimental therapy of human colon carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…CR-1 is overexpressed in a number of different types of human carcinomas and has been demonstrated to modulate the signaling of these pathways in human tumor cell lines in vitro (Adamson et al, 2002). In vivo, experiments have shown that tumor growth can be suppressed by downregulation of CR-1 using an antisense strategy Normanno et al, 1996Normanno et al, , 1999De Luca et al, 1997 or inhibition of CR-1's CFC signaling domain with an anti-CR-1 mouse monoclonal antibody or with an anti-EGF-like domain CR-1 rat monoclonal antibody Xing et al, 2004). These experiments validate that blockade of CR-1 can modulate tumor growth and points to CR-1 as a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…AR is expressed in several tissues, such as human ovary, placenta, lung, kidney, stomach, colon and breast (Johnson et al, 1992;Lejeune et al, 1993). Increased evidences strongly suggest that AR may function as a potential autocrine growth factor in tumoral as well as in their counterpart normal cells, such as prostatic (Sehgal et al, 1994), colonic (Johnson et al, 1992;Normanno et al, 1995), and mammary epithelial cells (Li et al, 1992;Normanno et al, 1994a, b). Moreover, overexpression of AR has been detected in several oestrogen-responsive and -unresponsive breast cancer cell lines as well as in approximately 80% of human primary breast carcinoma (Martinez-Lacaci et al, 1995;Visscher et al, 1997).…”
mentioning
confidence: 99%